UV and NIR-Responsive Layer-by-Layer Films Containing 6-Bromo-7-hydroxycoumarin Photolabile Groups. - Feeney, Matthew J.; Hu, Xiaoran.; Srinivasan, Rati.; Van, Nhi.; Hunter, Martin.; Georgakoudi, Irene.; Thomas, Samuel W., III. (Tufts University. Tisch Library., 2018)
This paper describes polyelectrolyte multilayer films prepared by the layer-by-layer (LbL) technique capable of undergoing dissolution upon exposure to either ultraviolet or near-infrared light. Film dissolution is driven by photochemical deprotection of a random methacrylic copolymer with two types of side chains: (i) 6-bromo-7-hydroxycoumarinyl esters, photocleavable groups that are known to have substantial two-photon photolysis cross sections, and (ii) cationic residues from the commercially available monomer N,N-dimethylaminoethyl methacrylate (DMAEMA) In addition, the dependence of stability of both unirradiated and irradiated films on pH provides experimental evidence for the necessity of disrupting both ion-pairing and hydrophobic interactions between polyelectrolytes to realize film dissolution. This work therefore provides both new fundamental insight regarding photolabile LbL films and expands their applied capabilities to nonlinear photochemical processes.